2018
DOI: 10.1158/1055-9965.epi-18-0306
|View full text |Cite
|
Sign up to set email alerts
|

Two HLA Class II Gene Variants Are Independently Associated with Pediatric Osteosarcoma Risk

Abstract: The genetic etiology of osteosarcoma remains poorly understood despite the publication of a genome-wide association study. Association between HLA genetic variants and risk of several cancers has been observed, but HLA variation is not well captured by standard SNP arrays. We genotyped 207 Californian pediatric osteosarcoma cases and 696 controls of European ancestry using a custom genome-wide array supplemented with approximately 6,000 additional probes across the MHC region. We subsequently imputed 4-digit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A separate case-only GWAS of osteosarcoma clinical characteristics among patients of European, African, and Brazilian ancestry identified a single nucleotide polymorphism (SNP) associated with osteosarcoma metastasis 5 . Common germline variants involved in DNA repair 6 , growth regulation 7,8 , antigen processing and presentation 9 , and telomere maintenance 10,11 pathways have also been implicated in osteosarcoma risk.…”
Section: Introductionmentioning
confidence: 99%
“…A separate case-only GWAS of osteosarcoma clinical characteristics among patients of European, African, and Brazilian ancestry identified a single nucleotide polymorphism (SNP) associated with osteosarcoma metastasis 5 . Common germline variants involved in DNA repair 6 , growth regulation 7,8 , antigen processing and presentation 9 , and telomere maintenance 10,11 pathways have also been implicated in osteosarcoma risk.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a study in osteosarcoma (with > 90% of primary diagnosis tumor cases) reported putative HLA associations, with several class II alleles claimed to be negatively ( DRB1*03:01 , DQB1*02:01 ) or positively ( DQA1*01:01 ) associated with disease risk; however, only odd ratio values were described but not allele frequencies ( 89 ). Furthermore, a genome-wide association study in one cohort did not identify a susceptibility locus within the HLA ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function enrichment analysis results revealed that HLA class II alleles may be a main impactive factor in osteosarcoma. HLA-DQA1 is also an HLA class II variant that has been reported to be associated with the osteosarcoma risks [ 31 ]. Profound understanding of those genes’ immunologic contribution to the etiology of osteosarcoma may be helpful for selecting rational therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%